POLITENESS STRATEGIES, LINGUISTIC MARKERS AND SOCIAL CONTEXTS IN DELIVERING REQUESTS IN JAVANESE - Sukarno, Sukarno (Universitas Pendidikan Indonesia, 2018)
Delivering request is not only influenced by linguistic factors, but also by socio-cultural factors. Some studies have reported the interaction between linguistic and socio-cultural factors in delivering requests in many different languages. However, this issue is rarely explored in Javanese (language). The aim of this study is to investigate the politeness strategies, the linguistic markers, and the social contexts commonly used to deliver requests in Javanese. The data were collected and sorted from the conversations among the Javanese people in Jember, East Java, Indonesia, when making speech acts to deliver requests. Having been sorted, the data were analysed using the deconstructive method to reveal the linguistic markers commonly used by the Javanese speakers to deliver requests and the social-cultural backgrounds which influence the choice of the politeness strategies. This research shows that (1) there are four types (most direct, direct, less direct, and indirect) of politeness strategies in Javanese, (2) there are four linguistic devices (sentence moods, speech levels, passive voice, and supposition/condition) as the markers of the politeness strategies and (3) the choices of the levels are strongly influenced by the social contexts (social distance, age, social status or power, and the size of imposition) among the tenors. The appropriate strategies for delivering requests in Javanese will make the communication among the interlocutors run harmoniously.Â